LGG-32. EVALUATION OF PEDIATRIC GLIOMA OUTCOME USING INTRAOPERATIVE MRI: A COHORT STUDY USING I-MiND (IMRIS MULTICENTER iMRI NEUROSURGERY DATABASE). Issue 2 (22nd June 2018) - Karsy, Michael; Cheshier, Samuel; Akbari, S Hassan; Limbrick, David; Leuthardt, Eric C; Evans, John; Smyth, Matthew D; Strahle, Jennifer; Leonard, Jeffrey; Brockmeyer, Douglas L; Bollo, Robert J; Kestle, John R; et al.
Abstract: INTRODUCTION: Gliomas in pediatric patients remain challenging to treat. Intraoperative MRI (iMRI) may be a method to improve resection volumes, avoid critical structures, and guide intraoperative therapy in real-time. METHODS: We analyzed pediatric patients (age ≤18 years) in the I-MiND (IMRIS Multicenter iMRI Neurosurgery Database) who underwent resection of pathology-confirmed gliomas. RESULTS: A total of 327 patients (mean age 9.7 ± 4.6, 56.3% male) were identified who underwent treatment (13 neurosurgeons; 5 academic centers). Most tumors were World Health Organization (WHO) grade I (63.3%) without prior resection (82.6%) and were 31.7 ± 21.4 mm in average largest dimension. Of the 300 patients that underwent iMRI, additional tumor was resected from 140 patients (42.8%). Of the 37 patients with specimen sent to pathology after iMRI, 33 show positive tumor pathology (89.2%). The average surgery and room times were 5.6 ± 2.1 and 7.6 ± 2.2 hours, respectively. Mean overall survival (OS) for WHO grade I, II, III, and IV tumors was 35.4 ± 31.2, 20.1 ± 18.6, 19.2 ± 11.4, and 10.1 ± 10.6 months, respectively. On survival analysis, WHO grade and extent of resection impacted both OS and progression free survival (p<0.05). For patients with WHO grade I, II, III and IV tumors, a gross total resection rate of 73.9%, 75.0%, 72.2%, and 37.5% was observed, respectively. CONCLUSIONS: We evaluated the largest multicenter study of pediatric gliomas treated using iMRI. Increased extent of resection improved OS and gross-total resection was achievable in the majority of patients. The majority of post-iMRI resected specimens included tumors. Continued refinement of iMRI-techniques in pediatric patients may help improve outcomes.